PEMANFAATAN MEDIA PEMBELAJARAN KREATIF DALAM USAHA MENINGKATKAN HASIL BELAJAR SISWA - Nurul Fitria; Fera Septi Anggara; Irvan Rista Randy (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Learning is an interaction between teachers and students which aims not only to convey knowledge but also develop attitudes, skills and values. The use of creative learning media is an effective solution for increasing students' motivation, interest and understanding of the material. Media such as interactive videos, educational dolls, and smart cards can help turn abstract concepts into more concrete and easy to understand ones. However, challenges such as limited facilities, lack of mastery of technology by teachers, and limited access to information still often occur. Possible solutions include technology training for teachers, alternate use of learning tools, and expanding digital access for students. By implementing the right strategy, the use of creative learning media can increase the effectiveness and quality of the teaching and learning process and support the creation of more innovative and interesting learning.